The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/cch.12861
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of nurturance within the parent–child relationship in resource‐constrained families

Abstract: Background Nurturing parents raise children in an engaged, flexible, emotionally expressive and supportive manner, which is associated with positive outcomes for children. While parenting research within the South African context is increasing, there is a lack of focus on nurturance within the parent–child relationship. Thus, this study sought to explore how parents nurture their children in resource‐constrained environments in South Africa. Method A qualitative approach with an exploratory research design was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The literature points to nursing care and peer support as potential factors protecting from developing depression. 41,42 We did not consider these variables. However, this field of research on children with CKD might prove vital.…”
Section: Limitationsmentioning
confidence: 99%
“…The literature points to nursing care and peer support as potential factors protecting from developing depression. 41,42 We did not consider these variables. However, this field of research on children with CKD might prove vital.…”
Section: Limitationsmentioning
confidence: 99%
“…Parental support in the prevention of depression was also studied. It was shown that a safe, supportive environment with engaged and responsive caregivers builds resilience and secure attachment in children-important factors playing a protective role against major life stressors, such as the presence of chronic disease [25][26][27]. Children with chronic diseases are especially dependent on parental support in many areas of their lives.…”
Section: Depression Among Children With Ckdmentioning
confidence: 99%
“…Parental support plays a significant role in a child's mental well-being [19,25]. It seems that parents-or at least a PCs-should be included when implementing these preventative strategies [15,19,25].…”
Section: Conclusion and Future Directions For Studies On Depression I...mentioning
confidence: 99%
See 1 more Smart Citation